1984
DOI: 10.1002/chin.198444148
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESIS OF A NOVEL SERIES OF (ARYLOXY)PROPANOLAMINES: NEW SELECTIVE β2‐BLOCKING AGENTS

Abstract: Durch Cycloaddition der den Verbindungen (I) entsprechenden Arine mit den Enolaten (II) erhält man die Schlüsselverbindungen (III) und (IV), die über die Phenole (V) in die Phenolether (VI) umgewandelt werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Caubère and colleagues have reported that di-and tetrahydrobiphenylenes showed cytotoxicity against human lymphoblasts and L1210 murine leukemia cell lines. [6][7][8] For the synthesis of hexahydrobiphenylenes, a facial [2+2] cycloaddition of benzyne with an enamide 9) and an enolate 10) has been reported under strong base conditions (Chart 1). The resultant hexahydrobiphenylenes could be converted to tetrahydrobiphenylenes under dehydration conditions.…”
mentioning
confidence: 99%
“…Caubère and colleagues have reported that di-and tetrahydrobiphenylenes showed cytotoxicity against human lymphoblasts and L1210 murine leukemia cell lines. [6][7][8] For the synthesis of hexahydrobiphenylenes, a facial [2+2] cycloaddition of benzyne with an enamide 9) and an enolate 10) has been reported under strong base conditions (Chart 1). The resultant hexahydrobiphenylenes could be converted to tetrahydrobiphenylenes under dehydration conditions.…”
mentioning
confidence: 99%